TEL/AML-1 dimerizes and is associated with a favorable outcome in childhood acute lymphoblastic leukemia - McLean, Thomas W.; Ringold, Sarah; Neuberg, Donna; Stegmaier, Kimberly; Tantravahi, Ramana; Ritz, Jerome; Koeffler, H. Phillip; Takeuchi, Seisho; Janssen, Johannes W. G.; Seriu, Taku; Bartram, Claus R.; Sallan, Stephen E.; et al. (Blood, 1996)
Polymerase chain reaction-based screening of childhood acute lymphoblastic leukemia (ALL) samples showed that a TEL/AML 1 fusion transcript was detected in 27% of all cases, representing the most common known gene rearrangement in childhood cancer. The TEL/AML1 fusion results from a t(12;21)(p13;q22) chromosomal translocation, but was undetectable at the routine cytogenetic level. TEL/AML1-positive patients had exclusively B-lineage ALL, and most patients were between the ages of 2 and 9 years at diagnosis. Only 3/89 (3.4%) adult ALL patients were TEL/AML 7-positive. Most importantly, TEL/AML 1-positive children had a significantly lower rate of relapse compared with TEL/AML 1-negative patients (0/22 ν 16/54, P = .004). Co-immunoprecipitation experiments demonstrated that TEL/AML-1 formed homodimers in vitro, and heterodimerized with the normal TEL protein when the two proteins were expressed together. The elucidation of the precise mechanism of transformation by TEL/AML1 and the role of TEL/AML1 testing in the treatment of childhood ALL will require additional studies.